Features of invulerse pendulum model using high-speed run-up in javelin throwing - Motoyama, K.; Urita, Y.; Kintaka, H.; Maeda, A. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
This study uses three-dimensional motion analysis to determine features of the throwing motion in male javelin throwers. Run-up speeds were compared and features of the inverse pendulum model were determined using three-dimensional motion analysis. The results showed that run-up speed correlated with throwing distance. As run-up speed increased, the pendulum angle at L-on enlarged and tilted backwards (p < .01) after the width of the pendulum increased during the double-support phase. We presumed that the enlarged backward tilt converted a large amount of energy to increase the speed of run-up at L-on.